Chaplain Discovers TS Golden Bear is Vessel he Launched - Vallejo News Chronicle (Vallejo News Chronicle)
When the TS Golden Bear leaves Morrow Cove tomorrow in its new role of Friend Ship en route to hungry Europe, its departure will be witnessed by at least one Naval official who was present when the vessel first hit the cold waters of Narrangansett Bay at its launching December 11, 1944, Comdr. Ray Cook (ChC) USN, senior chaplain at Mare Island Naval Shipyard, today recalled events of that overcast, drizzly morning at Providence, R.I., when he delivered the christening address just before the bottle of champagne hit the attack transport's bow.